Trauma dan Pemulihan Relasional antara Manusia dan Naga: Relevansi Film Live-Action How to Train Your Dragon (2025) dalam Pembelajaran Bahasa dan Sastra Indonesia - Anida Emil Hartantri; Anas Ahmadi (Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
This study examines the representation of trauma and relational healing between humans and dragons in How to Train Your Dragon (2025) and its relevance to Indonesian language and literature education. The study aims to identify forms of trauma, explain the process of relational recovery, and explore the pedagogical potential of the film as a learning resource. Using a qualitative descriptive approach, the analysis applies content analysis based on trauma theory proposed by Caruth (1996) and LaCapra (2001), as well as Haraway’s posthumanist perspective (2008). The findings indicate that the live-action version presents trauma more concretely than the animated version through the visualization of physical injuries, expressions of fear, and relational distance between humans and dragons. Trauma is represented not only as an individual psychological experience but also as a collective and ecological phenomenon reflected in symbolic violence toward dragons and cultural pressure on humans. The relationship between Hiccup and Toothless illustrates a process of working through characterized by empathy, trust, and cross-species ecological reconciliation. These findings suggest that the film can be utilized as a multimodal text in Indonesian language and literature education to develop emotional literacy, ecological literacy, and literary appreciation skills.